Specification for low alloy electrodes for flux cored arc welding (American Welding Society, 2010)
This specification prescribes the requirements for classificaiton of low-alloy steel electrodes for flux cored arc welding. The requirements include chemcial composition and mechanical properties of the weld metal and certain usability characteristics. Optional, supplemental designators are also included for improved toughness and diffusible hydrogen. Additional requirements are included for standard sizes, marking, manufacturing, and packaging. A guide is appened to the specification as a source of information concerning the classification system employed and the intended use of low-alloy steel flux cored electrodes.